Factores relacionados a cáncer gástrico en un hospital público de Huánuco - Eulogio Valenzuela, Frida Katerina (2018)
Introduction: The objective of the present study was to determine the relationship between all Helicobacter pylori infection, socio economic level and dietetic factors, and gastric cancer in Regional Hospital Hermilio Valdizan - Huanuco. Methods: Observational Case-Control study. In a first time we used an instrument over de records in the hospital, then we met parents to complete the information. Furthermore, we toke blood samples to determine Helicobacter pylori infection thru ELISA IgG test. The statistical analysis was throughout software SPSS 15.0 and EPIDATA. Results: It was found 135 cases of endoscopically diagnosed stomach cancer and 135 randomized controls entries (N=270). 140 (51.9%) patients were male.188 (69%) patients were positive to Helicobacter pylori ELISA IgG Test. It was found statistically significant association between stomach cancer and Helicobacter pylori infection, male sex, age major than 60 years old and adding extra salt to food. There was not association between stomach cancer and social class, family history, place of provenance and diet. Conclusions: Helicobacter pylori infection, male sex, being more than 60 years old, and extra salt adding to food were risk factor to develop stomach cancer. Socioeconomic level, family history, place of provenance and diet were not risk factors to develop stomach cancer.